Meta Analisis Implementasi Computational Thinking untuk Meningkatkan Hasil Belajar Ipas di Sekolah Dasar - Dina Apriana; Ni Ketut Suarni; I Gede Margunayasa; Muhammad Hudri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to analyze relevant research in implementing the computational thinking approach to improve learning outcomes in Integrated Science (IPAS) at the Elementary School level. The study adopts a meta-analysis approach with data collection conducted through searching Google Scholar or Google Scholar and Mendeley using the keywords computational thinking, learning outcomes, and science education in elementary schools. The search yielded a total of 7 articles that utilized the computational thinking approach in teaching science at the elementary school level, employing qualitative research methods. The findings of the study indicate that the implementation of computational thinking in IPAS instruction at the Elementary School level can provide significant benefits in developing critical thinking skills, problem-solving abilities, teamwork, learning interest, and students' digital readiness. Therefore, it can be concluded that the positive implementation of computational thinking contributes to improved learning outcomes and skill development in students. The results of this research are expected to serve as recommendations and a foundation for enhancing students' learning outcomes through the application of computational thinking in the teaching and learning process. Keywords: Computational Thinking, Learning Outcomes, Science, Elementary School